Efficacy of artificial intelligence-based skin analysis for calculating wrinkle improvement and skin firmness after simultaneous radiofrequency and high-intensity focused ultrasound therapy: a retrospective clinical study - Woohyuk Yoon; Hea Kyeong Shin (Archives of Aesthetic Plastic Surgery)
Background Quantitative skin assessments have transitioned from subjective evaluations to objective approaches. However, clinical application has remained limited due to high costs and reliance on specialized equipment. High-intensity focused ultrasound and radiofrequency are the two most widely used noninvasive modalities for skin tightening and wrinkle improvement. This study investigated investigate the efficacy of artificial intelligence (AI)-based skin analysis as a more accessible and cost-effective tool for assessing skin firmness and wrinkle improvement. Methods A retrospective analysis was conducted on 34 patients treated simultaneously with high-intensity focused ultrasound and bipolar radiofrequency between January and February 2025. AI-based skin assessments, evaluating firmness and wrinkle scores, were obtained pre-treatment, immediately post-treatment, and at a 2-month follow-up. Standardized clinical photographs were independently evaluated by two blinded human raters. Logistic regression and correlation analyses were conducted to determine alignment between AI and human evaluations. Results AI analysis showed significant improvements in both firmness and wrinkle scores immediately after treatment and at the 2-month follow-up (P<0.05). Human evaluations demonstrated high inter-rater agreement (Cohen’s κ=0.72–0.91). Logistic regression analyses indicated that changes in AI scores significantly predicted human-rated treatment effectiveness at both time points (area under the curve [AUC] for firmness=0.86; AUC for wrinkles=0.73–0.93). Spearman correlation coefficients and the Mann-Whitney U test further supported strong alignment between AI and human assessments. Conclusions This study validates the clinical utility of AI-based skin analysis as a reliable quantitative measure for evaluating wrinkle improvement and skin tightening following energy-based rejuvenation treatments. Its predictive validity aligns well with expert human judgment, particularly at delayed follow-up.